The value of LH maximum level in predicting optimal oocyte yield following GnRH agonist trigger - Lee, William Hao-Yu; Lin, Kuan-Ting; Hsieh, Yun-Chiao; Kao, Tzu-Ching; Huang, Ting-Chi; Chao, Kuang-Han; Chen, Mei-Jou; Yang, Jehn-Hsiahn; Chen, Shee-Uan (Frontiers in Endocrinology, 2023)
Question: Does the maximum LH level (LH max) during controlled ovarian stimulation play a role in predicting optimal oocyte yield following GnRH agonist trigger only? Answer: The LH max level may represent LH reserve in controlled ovarian stimulation (COS) following GnRH agonist trigger only. What is known already: A GnRH agonist ovulation trigger may result in an inadequate oocyte yield in a small subset of patients. The risk factors include a high or low BMI, prolonged oral contraceptive pill use, low LH levels on the start day and on the trigger day of contorl ovarain stimulation. Method: A retrospective review was conducted on all antagonist protocols or PPOS protocols that were triggered with a GnRH agonist only between May 1st, 2012 and December 31st, 2022. At a university-based tertiary fertility center, a total of 1077 IVF/ICSI cycles were conducted using a GnRH antagonist protocol or PPOS for controlled ovarian stimulation (COS) following induction of oocyte maturation with GnRH agonist. Subjects were divided into three groups, depending on basal LH level and LH maximum level. Group 1 : consistently low LH levels throughout COS; Group 2 : low basal LH level with, high LH max level during COS; Group 3 : consistently high LH levels throughout COS. Results: The average age was 34.8±4.3 years, and the mean oocyte yield was 89.4±13.7%. The suboptimal response to GnRH agonist trigger cut-off (<5th percentile) was 60.7 %, which was exhibited by 40 patients. Following confounder adjustment, multivariable regression analysis showed that Group 1 (cycles with consistently low LH levels throughout COS) remain an independent predictor of suboptimal response. (OR: 6.99). Group 1 (b=-12.72) and BMI (b=-0.25, 95%CI -0.5 -0.004) were negatively assicaited with oocyte yield rate. Patient in group 2 (basal LH <2.2IU.L, with LH max >2.2IU/L) and group 3 (LH max> 2.2 IU/L throught COS) remain no difference in any clinical outcomes. Conclusion When considering trigger agents (agonist only or dual trigger) in hyper-responders, we propose a new strategy that utilizes the maximum LH (not just the basal or trigger-day LH level) as a reference to assess LH reserve and avoid inadequate oocyte rate.